2007
DOI: 10.1007/s10495-007-0754-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathological apoptosis in the developing brain

Abstract: More than half of the initially-formed neurons are deleted in certain brain regions during normal development. This process, whereby cells are discretely removed without interfering with the further development of remaining cells, is called programmed cell death (PCD). The term apoptosis is used to describe certain morphological manifestations of PCD. Many of the effectors of this developmental cell death program are highly expressed in the developing brain, making it more susceptible to accidental activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(140 citation statements)
references
References 226 publications
4
130
1
5
Order By: Relevance
“…In this study, caffeine increased GSK3β phosphorylation at Ser9; this regulation was controlled by PKA. In normal cells, constitutively active GSK3β negatively regulates the proto-oncogenic protein, β-catenin, via phosphorylation-induced degradation, limiting its expression (Blomgren et al, 2007). Interestingly, in this study, despite an induction of GSK3β phosphorylation (at Ser9), we observed no increase in β-catenin expression after caffeine treatment.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In this study, caffeine increased GSK3β phosphorylation at Ser9; this regulation was controlled by PKA. In normal cells, constitutively active GSK3β negatively regulates the proto-oncogenic protein, β-catenin, via phosphorylation-induced degradation, limiting its expression (Blomgren et al, 2007). Interestingly, in this study, despite an induction of GSK3β phosphorylation (at Ser9), we observed no increase in β-catenin expression after caffeine treatment.…”
Section: Discussioncontrasting
confidence: 67%
“…In previous studies, regulation of p21 expression and Rb phosphorylation were shown to be responsible for cell cycle arrest in the G 0 /G 1 phase in glioma cells (Choi et al, 2008;Tsai et al, 2006). GSK3 is a multifunctional serine/threonine kinase that reg β ulates various cellular pathways involved in the cell cycle, proliferation, differentiation, and apoptosis (Blomgren et al, 2007;He et al, 2003;Miyashita et al, 2009). GSK3β activity is negatively regulated by phosphorylation on Ser9 by Akt, PKA, and PKC (Blomgren et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AIF has been shown to be involved in PCD during early embryogenesis (Joza et al, 2001;Cheung et al, 2006) and in injury-induced cell death in the neonatal and adult brain (Blomgren et al, 2007;Cao et al, 2007). Finally, because we show here that neuronal PCD in the absence of Apaf-1 exhibits an autophagic morphology, we also examined whether normal neuronal PCD during development is perturbed by the loss of one of the key genes involved in autophagy, ATG7 Levine and Yuan, 2005;Komatsu et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…При этом форма клеточной гибели зависит от степени гипоксии-ишемии [26]: при тяжелой -некроз, при умеренной -апоптоз [18]. Активация апоптоза обу-словлена тем, что запрограммированная гибель клеток у человека в первые дни после рождения представляет собой ведущий механизм нейропластичности, поэтому максимально проявляется именно в этот период времени [27,28]. В ряде работ экспериментаторами выделен тре-тий, промежуточный, тип погибших нейронов -гибрид-ный, который в ядрах имеет признаки апоптотической гибели, а в цитоплазме -некротический тип [18,29].…”
Section: патофизиологические механизмы гипоксически-ишемических поражunclassified